Implementation of extreme programming in field service management system development to enhance efficiency in construction projects - Sihombing, Denny Jean Cross (SEAN Institute, 2024)
This research addresses efficiency challenges in field service management on construction projects by applying the Extreme Programming (XP) Method. Faced with the complexity of construction projects and the limitations of conventional software development methods, this research focuses on applying XP principles as an adaptive and responsive approach. The results showed that the application successfully provided an efficient solution and increased user satisfaction through the stages of data collection, application development using XP, and user acceptance analysis. User data reflected that features such as real-time monitoring, adaptive planning, task management, and field change notifications were perceived to contribute to operational efficiency positively. Out of 50 users, about 85% expressed high satisfaction with the app. The main contribution of this research is validating XP's success in overcoming the dynamics of construction projects and providing solutions that fit the field context. Thus, this research not only provides deep insight into the effectiveness of XP in construction software development but also offers practical contributions to improving the efficiency and responsiveness of construction project management.